2020
DOI: 10.1002/cam4.3569
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial assessing impact of probiotic supplementation on gut microbiome and clinical outcome from targeted therapy in metastatic renal cell carcinoma

Abstract: Studies suggest a link between the gut microbiome and metastatic renal cell carcinoma (mRCC) outcomes, including evidence that mRCC patients possess a lower abundance of Bifidobacterium spp. compared to healthy adults. We sought to assess if a Bifidobacterium‐containing yogurt product could modulate the gut microbiome and clinical outcome from vascular endothelial growth factor‐tyrosine kinase inhibitors (VEGF‐TKIs). mRCC patients initiating VEGF‐TKIs, regardless of the line of therapy, were randomized to prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 21 publications
0
41
1
1
Order By: Relevance
“…Fecal microorganisms and metabolites are often affected by diet ( 34 ). In this study, the subjects were not given a standardized diet like other studies ( 3 ) but kept the original eating habits, which is the limitation of this study. However, non-invasive research can be overcome by expanding the sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecal microorganisms and metabolites are often affected by diet ( 34 ). In this study, the subjects were not given a standardized diet like other studies ( 3 ) but kept the original eating habits, which is the limitation of this study. However, non-invasive research can be overcome by expanding the sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a link between the gut microbiota and metastatic RCC (mRCC). Evidence showed that RCC patients have a lower abundance of bifidobacteria , compared with healthy adults ( 3 ). However, it needs experimental verification about whether there is a connection between the gut microbiota and RCC needs to.…”
Section: Introductionmentioning
confidence: 99%
“…In a human study, the administration of L. rhamnosus HN001 and B. longum BB536 increases the abundance of A. muciniphila (Toscano et al 2017). Dizman et al demonstrated that fermented milk with B. animalis could improve the abundance of A. muciniphila in metastatic renal cell carcinoma patients (Dizman et al 2021). These species may interact with A. muciniphila although the interaction mechanism is unknown.…”
Section: Interaction With Bacteriamentioning
confidence: 99%
“…An interesting randomized controlled trial assessed whether a Bifidobacterium -containing yogurt product could modulate the gut microbiome and clinical outcomes of metastatic renal cell carcinoma (mRCC) patients initiating vascular endothelial growth factor-tyrosine kinase inhibitors (VEGF-TKIs) [ 95 ]. They randomized patients into the probiotic-supplemented group (receiving two servings of 120g probiotic yogurt product daily) or the probiotic-restricted control group.…”
Section: Nutritional Interventions Modulating Gut Microbiota During Cancer Therapymentioning
confidence: 99%
“…Additionally, in patients with clinical benefit (i.e., response of either complete/partial response or stable disease for over 6 months), Barnesiella intestinihominis and Akkermansia muciniphila were significantly more abundant compared with patients with no clinical benefit. [ 95 ]. This is the first study prospectively assessing the impact of fermented food on clinical outcomes in cancer patients undergoing chemotherapy.…”
Section: Nutritional Interventions Modulating Gut Microbiota During Cancer Therapymentioning
confidence: 99%